On determination of maximum bending moments for assignment of global hull strengthparameters - Pavel Ye. Burakovsky (Труды Крыловского государственного научного центра, 2020)
Object and purpose of research. This paper investigates global strength implications of extreme operating conditions (stern emergence and bow greenwatering). Materials and methods. This study was performed as per the methods of naval structural mechanics, ship theory and applied programming. Main results. This paper suggests a calculation method for additional bending moments in the assessment of global longitudinal hull strength in the conditions of bow greenwatering and stern emergence. Conclusion. This study determines hull bending moments in the conditions of bow greenwatering and stern emergence, highlighting the imperfections of existing approaches to assignment of global strength parameters for hulls. The findings of this work could be helpful in global strength assessment of ships in extreme operating conditions.